(untitled) (Eurasian Journal of Engineering and Technology, 2024)
In this article, the peculiarities of the architectural architecture of Bukhara, the layout of many mosques and madrasahs, the architectural solution of shopping domes, aspects, architectural methods and features that have not lost their appearance, analysis explained based on.